Retroperitoneal fibrous tumor recurring as lung metastases after 10 years: a case report - Kozue Matsuishi; Kojiro Eto; Atsushi Morito; Hirokazu Hamasaki; Keisuke Morita; Satoshi Ikeshima; Kei Horino; Shinya Shimada; Hideo Baba (Surgical Case Reports)
Abstract Background Solitary fibrous tumor (SFT) is a relatively rare mesenchymal tumor that mainly affects adults. Its prognosis is good after curative resection, but distant recurrences after 10 years or longer have been reported. Recurrent SFT usually arises as a local lesion; distant metastasis is rarely reported. Here, we report lung metastases that recurred a decade after excising a retroperitoneal primary SFT. Case presentation A 44-year-old woman had an SFT resected from her right retroperitoneum at our hospital. Ten years later, at age 54, she underwent a lung resection after CT showed three suspected metastases in her left lung. All three were histologically diagnosed as lung metastases from the retroperitoneal SFT. However, whereas the primary SFT had 1–2 mitotic cells/10 high power fields (HPF), the metastatic lesion increased malignancy, at 50/10 HPF. Conclusion Patients who have had resected SFTs should be carefully followed up, as malignancy may change in distant metastasis, as in this case.